BOOK REVIEW: PRESENTING IN ENGLISH: A PRACTICAL GUIDE - Athapaththu, Pasan (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
Authored cautiously, keeping in mind the individuals who find it challenging to deliver presentations in English, Presenting in English: A Practical Guide by Dick Smakman is a potential candidate to occupy space on the bookshelf of any student genuinely seeking straightforward advice for their presentations. As presentations are a powerful persuasive tool (Duarte, 2010) and the most transferable of all other skills (Van Emden Becker, 2016), a majority of modules in educational programmes have allocated space for a component on presentation skills (Grieve et al., 2021).